THE PLASTICITY OF MATTER OR TO THE NATURE OF EXPERIMENTATION IN THE PROSES OF JACHYM TOPOL, EDMUND HLATKY AND ZIEMOWIT SZCZEREK (SKETCH OF THE ISSUE) - Mitka, Marek (Bohemica Olomucensia, 2021)
The study focuses on the interpretation of key prosaic works in Czech, Slovak and Polish literature after 1989, respectively after 2000. It notices Jachym Topol's iconic novel Sister, two collections of shorter proses by Slovak writer Edmund Hlatky (Slava a tajomstvo and Jesenny opar) and two proses by Polish novelist and reporter Ziemowit Szczerek (Sivy dym and Pec verejna: Bezpolstie), which penetrates into the consciousness of Polish readers only a few years ago. In the analysis of these works, the author of the study focuses on experimental tendencies and procedures, which in all three cases are related to the modeling of language as the basic material of a literary work. The author pays particular attention to the special types of neologisms, slang, slang distortions and their functionality in evoking comics, absurdity, chaos etc.
Keywords: Postmodernism; experimental writing; poetics of prosaic text; interpretation; Central European literatures after 1989; J. Topol; E. Hlatky; Z. Szczerek